Desain User Interface Pada Sistem Penilaian Mandiri Aplikasi Di Diskominfo Provinsi Jawa Barat - Wahyudi, Rizmya Bunga; purfini, apriani puti (Program Studi D3 Komputerisasi Akuntansi Fakultas Teknik dan Ilmu Komputer , Universitas Komputer Indonesia, 2023)
The West Java Province Application Self-Assessment System is an application management system that has the domain prov.jabar.go.id. This system makes the work of one of the fields in Diskominfo Prov easier. West Java regarding the management of applications that previously spent a lot of time managing one application. In addition, this system also makes application management more effective and efficient. In terms of design solutions, User Interface Design (UI) was chosen as a solution to the problems faced by regional device users so that they can easily access system information. The purpose of this user interface (UI) design is to communicate the available system functions so that users can understand and use the system and have satisfaction and comfort in using the application. In building the design of this application, the authors apply the method of identification, implementation, interviews and evaluation which aims to fully understand what is needed from direct observations in the field. By designing the user interface (UI) for this selfassessment system, it is hoped that users will feel satisfied and comfortable in using the application. Key words: Design, User Interface, Application